THE WORD â€œSHOOTâ€ ANALYZED BY NATURAL SEMANTIC METALANGUAGE - Prabhaswari, Putu Indry; Budiarsa, Made; Puspani, Ida Ayu Made (International Journal of Language and Literature, 2021)
This study is focusing on the mapping of word shoot meanings. The collected data was qualitatively analyzed, it was starting by reading some sources, finding a word to be analyzed, reading carefully the source text and the target text, taking note, analyzed the text by NSM approach by Wierzbicka (1999). The data in this writing was taken from Colour Magazine Garuda Indonesia and used one of the prevalent comic series of Tintin entitled The Adventures of Tintin: Tintin in America and Tintin the shooting star. The technique of this study were three steps, they are finding the word which want to analyzed, read the text carefully, finding the word with its translation which want to discuss, directly noted the word which was according to the topic. The result of this study showed that the findings of three meanings of one word shoot. Some of the translation could convey the meaning therefore the reader in target language is easily read and understood.